2017
DOI: 10.1002/1873-3468.12772
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for cancer‐associated inactivation of NQO1 due to P187S and its reactivation by the consensus mutation H80R

Abstract: The cancer-associated P187S polymorphism in the NAD(P)H:quinone oxidoreductase 1 (NQO1) abolishes enzyme activity by strongly reducing FAD binding affinity. A single mammalian consensus mutation (H80R) protects P187S from inactivation. To provide mechanistic insight into these effects, we report here a detailed structural and thermodynamic characterization of FAD binding to these NQO1 variants. Our results show that H80R causes a population shift in the conformational ensemble of apo-P187S, remodelling the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…Cell sensitivity to ansamycin inhibitors of HSP90 was also associated with expression of NQO1 encoding NAD(P)H:quinone oxidoreductase 1 that converted these compounds to hydroquinone to enhance their activity by increasing hydrogen bonding [99]. It was reported that NQO1 P187S variant exerted diminished activity compared with wild-type NQO1 [99], but genetic alterations affecting a His 80 residue in this protein could compensate for P187S substitution [100]. Loss of NQO1 expression and acquisition of NQO1 P187S variant contributed to the development of resistance to 17-AAG [101].…”
Section: Benzoquinone Inhibitorsmentioning
confidence: 99%
“…Cell sensitivity to ansamycin inhibitors of HSP90 was also associated with expression of NQO1 encoding NAD(P)H:quinone oxidoreductase 1 that converted these compounds to hydroquinone to enhance their activity by increasing hydrogen bonding [99]. It was reported that NQO1 P187S variant exerted diminished activity compared with wild-type NQO1 [99], but genetic alterations affecting a His 80 residue in this protein could compensate for P187S substitution [100]. Loss of NQO1 expression and acquisition of NQO1 P187S variant contributed to the development of resistance to 17-AAG [101].…”
Section: Benzoquinone Inhibitorsmentioning
confidence: 99%
“…NQO1apo exists as a stable and expanded dimer characterized by significantly large conformational flexibility [76,78,79,80,119,130,131,132]. Although no high resolution structural model is available for this state, recent kinetic studies using hydrogen-deuterium exchange mass spectrometry (HDXMS) have identified a minimal stable core that holds the protein dimer while most of the protein exists forming a highly dynamic structural ensemble, including the FAD and substrate binding sites in non-competent states for binding [129].…”
Section: Changes In Nqo1 Stability Structure and Dynamics Upon Liganmentioning
confidence: 99%
“…Binding of FAD triggers a large conformational change leading to compaction of the protein dimer, increase in ordered secondary structure, overall conformational stabilization and a large decrease of protein dynamics that is sensed in almost the entire protein structure [78,79,80,119,129,130,131,133]. This NQO1holo state is amenable for high-resolution structural studies [81]( Figure 6A).…”
Section: Changes In Nqo1 Stability Structure and Dynamics Upon Liganmentioning
confidence: 99%
See 2 more Smart Citations